Pengaruh Evaluasi Moral dalam Melejitkan Potensi Anak Penghafal Quran di Rumah Quran Abi 'nd Umi - Jaka Samudra, Muhammad; Fauzi Nazara, Ahmad; Rizki, Rizki; Hasanuddin, Hasanuddin (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to describe how to foster students in moral evaluation to jump-start the potential of children who memorize the Qur'an and the application of moral evaluation in boosting the potential of children memorizing the Qur'an at the House of Al-Qur'an Abi 'nd Umi. The research method used is a qualitative method to analyze data, develop literacy, collect continuous data, interviews, and see directly the object under study. This research was conducted at the Qur'an Abi 'nd Umi House, Jalan Asrama Ringroad, Bumi Seroja Permai Complex, Blok J 63 which is homeschool-based under the guidance of Ustadz Muhammad Anshari, Lc. M.TH Al Hafidz (Holder of the 30th Sanad Al-Qur'an from Sheikh Dr. Mahir Munajjid Ad-Dimasyqi) for junior high and high school levels. The information in this study includes the object of children memorizing the Koran, education staff, one owner, two teachers and two musyrifs. The results showed that eight people had the potential to be fast in memorizing the Qur'an due to the influence of the moral evaluation carried out. By providing moral guidance to students with strict rules, advice that makes an impression and using soft and straightforward words when talking to them, as well as implementing evaluations carried out by formulating goals, planning, making comparisons, and the techniques used have been effective. The effect of moral evaluation in boosting the potential of children who memorize the Koran at home Al-Quran abi 'nd umi under study is appropriate to apply.